Guanosine diphosphate-mannose:GlcNAc2-PP-dolichol mannosyltransferase deficiency (congenital disorders of glycosylation type Ik): five new patients and seven novel mutations. Issue 11 (2nd August 2010) - Dupré, T; Vuillaumier-Barrot, S; Chantret, I; Yayé, H S; Le Bizec, C; Afenjar, A; Altuzarra, C; Barnérias, C; Burglen, L; de Lonlay, P; Feillet, F; Napuri, S; et al.
Abstract : Background: In type I congenital disorders of glycosylation (CDG I), proteins necessary for the biosynthesis of the lipid-linked oligosaccharide (LLO) required for protein N-glycosylation are defective. A deficiency in guanosine diphosphate-mannose: GlcNAc2 -PP-dolichol mannosyltransferase-1 (MT-1) causes CDG Ik (OMIM 608540), and only five patients, with severe multisystemic clinical presentations, have been described with this disease. Objective: To characterise genetic, biochemical and clinical data in five new CDG Ik cases and compare these findings with those of the five previously described patients. Methods: LLO biosynthesis was examined in skin biopsy fibroblasts, mannosyltransferases were assayed in microsomes prepared from these cells, and ALG1 -encoding MT-1 was sequenced at the DNA and complementary DNA levels. Clinical data for the five new patients were collated. Results: Cells from five patients with non-typed CDG I revealed accumulations of GlcNAc2 -PP-dolichol, the second intermediate in the biosynthesis of LLO. Assay of MT-1, -2 and -3, the first three mannosyltransferases required for extension of this intermediate, demonstrated only MT-1 to be deficient. DNA sequencing of ALG1 revealed nine different mutations, seven of which have not been previously reported. Clinical presentations are severe, with dysmorphias, CNS involvement and ocular disturbances being prevalent. Conclusions: 5 patients with CDG Ik are described, and their identification reveals that in France, this disease and CDG Ib (mannose phosphate isomerase deficiency: OMIM 602579) are the most frequently diagnosed CDG I after CDG Ia (phosphomannomutase 2 deficiency: OMIM 601785) and substantiate previous observations indicating that this disease presents at the severe end of the CDG I clinical spectrum.